Effect of Type of Adhesive Material on the Strength of Bullet-Proof Glass: A Parametric Study - Thakur, Nitin; Bharj, Rabinder Singh; Kumar, Pramod (Asian Review of Mechanical Engineering, 2019)
Laminated glass armors play key roles in defense and architecture due to its high aesthetics and inviolability. Armor designing is based upon Wave propagation phenomena produced during a high velocity impact. Laminated glass or bulletproof glass usually comprises of two or more glass sheets bonded by an interfacial layer of adhesives and backed with a high strength ductile polymer (polycarbonate). Typical bonding agents include either high performance adhesives or synthetic resins such as Polyurethane or Polyvinyl butyral (PVB). Recent literature review infers that the ballistic performance of armors is markedly influenced by both the type and thickness of bonding agents, which may be explained by the acoustic impedance mismatch between laminate materials. This paper documents a novel simulation parametric study, considering the material of adhesive layer and thus concluding that, type of adhesive layer plays an important role in maintaining the strength of the bullet-resistant glass. This study took into account the effect of three types of bonding agents (epoxy, polyurethane and PVB) having constant thickness of 1.50 mm, on the ballistic performance of the laminated glass, against AK-47 ammunition projectiles. Simulations were performed in Ansys Explicit Dynamics using a finite element method approach.